Impact of perceived social media marketing activities on brand and value consciousness: Roles of usage, materialism and conspicuous consumption - Rageh, Ahmed; Nguyen, B.; Melewar, T. (2018)
Copyright © 2018 Inderscience Enterprises Ltd. This research investigates the impact of perceived social media marketing activities on brand- and value consciousness. It further examines the effect of social media usage on materialism, brand consciousness and conspicuous consumption, as examining materialism-centric behaviour is becoming important in a consumption-based economy. A self-administered questionnaire was developed and administered to a sample of 346 undergraduate students. Two different research models are tested and confirmed. The findings of this research indicated that perceived social media marketing activities have a significant effect on brand loyalty; brand consciousness and value consciousness mediate the relationship between perceived social media marketing activities and brand loyalty. Moreover, evidence supports the idea that the greater the use of social media, the greater the tendency towards materialism and conspicuous consumption. This study confirms the growing importance of perceived social media marketing activities in envisioning brand loyalty and provides insights on impact of social media on materialism and conspicuous consumption.